Fabrication of novel hybrid composite La2‐xCoxCuO4 electrode for high performance supercapacitors. (3rd March 2019) - Rafique, Muhammad; Sadaf, Iqra; Nabi, Ghulm; Bilal Tahir, Muhammad; Khan, Muhammad Isa
Summary: Hybrid composites La2‐x Cox CuO4 (x = 0, 0.1, 0.2, and 0.3) are prepared using one‐step simple hydrothermal route as electrodes for supercapacitors. The effect of varying cobalt content on morphological, structural, and electrochemical properties has been explored using X‐ray diffraction, scanning electron microscopy, and cyclic voltammetry, respectively. The structural parameters obtained by X‐ray diffraction showed tetragonal phase of hybrid composite without any evident impurity phases. The analysis of morphological properties suggested a strong correlation with electrochemical properties, for instance, a relationship between fabric porous structures and electrochemically active sites for redox reactions and intercalation/de‐intercalation processes. The hybrid composite electrodes demonstrated high specific capacitance of the order of 1304 F/g at 10 mV/s scan rate and exhibited decreasing trend on increasing scan rate. Hybrid composites were also tested for their ability as an electrode of high performance supercapacitors in different aqueous electrolytes, i. e, KOH, H2 SO4, and Na2 SO4 to optimize the best compatible electrolyte. The composite electrode material showed excellent cyclic stability and 98% capacitance retention for 1 A/g after 2000 cycles. The remarkable performance of hybrid composite electrode entails its potential for commercial applications of supercapacitors. Abstract : A novel La2‐x Cox xCuO4 (x = 0.1, 0.2, 0.3) hybrid composite is synthesized using a facile and one-step hydrothermal synthesis method, and to the best of our knowledge, the synthesis of this composite as well as supercapacitor electrode is reported first ever. The morphology and structure dependence of composite on cobalt quantity are reported, which represent the increase in specific capacitance and maximum specific capacitance 1304 Fg −1 at 10 mVs −1 scan rate in 6M KOH as electrolyte solution is reported. The electrochemical performance of hybrid composites was investigated for 6M KOH, 1M H2 SO4, and 1M Na2 SO4 electrolytes to optimize the best electrolyte for this novel electrode and high performance supercapacitors.